Reproducibility and validity of the Portuguese Edmonton Frail Scale version in cardiac surgery patients - Castro, Maria de Lurdes (2023)
Funding text To Dr. Darryl Rolfson for his assistance throughout this work. To Dr. Isabel Fragata, former Anesthesiology Head of Department at Centro Hospitalar Universitário Lisboa Central, for her encouragement and support. To all the members of the panel for EFS Portuguese translation final version: Professor José Fragata, Professor Maria-Amália Botelho, Professor Pedro Pires Coelho, Dr. Isabel Fragata, Dr. Helena Barrios, Dr. Ângela Sá, Dr. Miguel Ferreira and Dr. César Magro. To Sandra André, from the Administrative Bureau in Cardiothoracic University Clinic at Centro Hospitalar Universitário Lisboa Central.